INFLUENCE OF FERTILIZERS ON ACCUMULATION OF HEAVY METAL IN SOIL AND PHYTO MASS OF GRAIN CROPS - V. B. Trots; D. A. Akhmatov; N. M. Trots (Зерновое хозяйство России, 2018)
It’s common knowledge that heavy metal (HM) can enter the soil together with fertilizers which contaminates agricultural landscapes. The purpose of the research is to study influence of fertilizers on accumulation and migration of Cd, Pb ,Zn, Cu, Co, Mn in soil and plants. The research was conducted during field experiments in chernozem (blacksoil). We studied two levels of plant fertilizing: the first one without fertilizers and the second one with fertilizing of norms of NPK. The fertilizers were distributed in the following way: spring wheat (Triticum vulgare) – N60P60K60; spring barley (Hordeum vulgare) and oats (Avena sativa) – N45P45K20; millet (Panicum miliaceum) – N30P40K40; peas (Pisum sativum) – N10P60K60; buckwheat (Fagopyrum esculentum) – N45P60K60.v We found out that fertilizing raises the amount of Сd, Рb Zn, Сu, Со and Мn on 10-36% in soil and increases mobility of Zn, Си, Со and Мn on 25%. The increase of fertilizing of spring wheat, barley, oats, millet and buckwheat reduces whole volume of HM migration in phyto mass on 5-30%.  But it also stimulates Pb migration in the plants of spring wheat, migration of Сd, Zn and Сu into bio mass of oats and barley, and migration of Cd and Mn into peas. The main portion of accumulated elements is stored in a root system of a plant, Zn and Cu are able to transport into inflorescence. The volume of HM accumulation in phyto mass of fertilized plants doesn’t exceed TLV.